Fillet Yield and Length-Weight Relationship of Five Fish Species From Lower River Benue, Makurdi, Nigeria - Okomoda Victor Tosin,; Sololmon Shola Gabriel,; Songbe, S. Wukatda,; Ikape, Simon I.,; Ikhwanuddin Mhd,; Abol-munafi Ambok Bolong, (Tropical Life Sciences Research, 2021)
The body characteristics and yield indices of Clarias gariepinus, Bagrus bajad, Synodontis nigrita, Labeo senegalensis, and Mormyrus rume from lower River Benue in Nigeria were determined in this study using sixty samples each for the fish species. Length, weight, and fillet correlations were also determined during the study. Results obtained showed that M. rume L. senegalensis and C. gariepinus had the highest percentage of edible parts (?55%) compared to the other species (?39%). Concerning correlations of the fillet with the morphological variables, results obtained suggest that fillet yield is independent of fish size (except for C. gariepinus which was positively correlated). Also, only samples of L. senegalensis showed isometric growth pattern; the other fish species had either positive (C. gariepinus and B. bajad) or negative (S. nigrita and M. rume) allometric growth. While the difference in fillet yield and body characteristics was attributed to the structural anatomy and other biological dynamics of the fishes, this study could not establish a connection between fillet yield and the length-weight relationship. It was concluded that M. rume L. senegalensis and C. gariepinus would be better export products because of their higher fillet yields.